The Nietzsche legacy in Germany, 1890-1990 - Aschheim, Steven E., 1942- (Weimar and now, 1992)
The twentieth century has seen countless attempts to appropriate the ideas of Friedrich Nietzsche for diverse cultural and political ends, but nowhere have these efforts been more sustained and of greater consequence than in Germany. In The Nietzsche Legacy in Germany, 1890-1990, Steven Aschheim offers a magisterial chronicle of the philosopher's presence in German life and politics from the turn of the century through the recent reunification. Beginning with the aesthetic frenzy of fin-de-siecle European culture, through the historical convulsions of the Weimar Republic and the Third Reich, Nietzsche, the philosopher who hoped he would never have disciples, emerges in Aschheim's account as a thinker whose work crucially influenced - and was recast to fit - a multitude of contradictory projects. Anarchists, feminists, Nazis, religious cultists, Socialists, Marxists, vegetarians, avant-garde artists, devotees of physical culture, and archconservatives are but some of the groups that marched under a Nietzschean banner. Aschheim explores the significance of Nietzsche not only for such well-known figures as Martin Heidegger, Thomas Mann, and Carl Jung, but also for more obscure thinkers such as the liberal Rabbi Cesar Seligmann, who coined the phrase "the will to Judaism," and the radical psychoanalyst and free love advocate Otto Gross. He provides a judicious and balanced account of the link between Nietzsche and National Socialism and explores the ubiquity of Nietzsche within the major tensions of contemporary German history. The philosopher's "untimely" thoughts are, as Aschheim shows, more relevant than ever to the moral, aesthetic, and intellectual challenges of our own age